Elemen pembentuk citra kota dalam kawasan stasiun kereta api di Kota Semarang - Lutfiana, Unsani; Rukayah, Siti (Jurnal Arsitektur Lansekap; Vol. 11, No. 1 April 2025DO - 10.24843/JAL.2025.v11.i01.p10, 2025)
Elements of City Image Formation in the Train Station Area in Semarang City . The increasingly dense development of public transportation in the city of Semarang, such as railway transportation which is integrated with other transportation, will influence the progress of the city or region related to character and identity in the form of the city's image. In the city image there are elements that form the city image proposed by Kevin Lynch (1960) such as paths, edges, districts, nodes and landmarks. The existence of the main train stations in Semarang City, namely Semarang Tawang Bank Jateng Station and Semarang Poncol Station, plays an important role in the development of public transportation, so it is necessary to understand the elements that form the image of the city in the area in order to understand the situation to be used as a reference for developing and improving the quality of the area. The research method used is qualitative research with a case study approach using primary data and secondary data with the final result being a description complete with supporting images. The results of the research are the condition of city image elements in the Semarang Tawang Bank Jateng Station Area and the Semarang Poncol Station Area which are needed to serve as a reference in developing the area.